2022
DOI: 10.1108/jd-02-2022-0030
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 pandemic on researcher collaboration in business and economics areas on national level: a scientometric analysis

Abstract: PurposeThe coronavirus disease 2019 (COVID-19) pandemic has greatly impacted society and academic life and research practices. This study is an attempt to comprehend whether a global emergency of COVID-19 pandemic has an impact on researcher international collaboration. The authors analyze the research collaboration before and after the beginning of the COVID-19 pandemic to understand how scientists collaborated within their own nation's borders and beyond.Design/methodology/approachThe authors analyze the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Cultural differences could possibly have shaped COVID-19 research collaboration in EMR countries, which can be explained by Hofstede's theory of cultural dimensions [ 62 ]. A recent study analyzing research collaboration in the area of business and economics by 11 countries, including Iran from the EMR, before and after the onset of the pandemic, showed that Hofstede's uncertainty avoidance domain significantly influences the characteristics of research collaboration networks [ 63 ]. Uncertainty avoidance explains how cultures adjust to change and cope with uncertainty [ 62 ], and the pandemic has caused major changes and uncertainties at all levels of society worldwide [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cultural differences could possibly have shaped COVID-19 research collaboration in EMR countries, which can be explained by Hofstede's theory of cultural dimensions [ 62 ]. A recent study analyzing research collaboration in the area of business and economics by 11 countries, including Iran from the EMR, before and after the onset of the pandemic, showed that Hofstede's uncertainty avoidance domain significantly influences the characteristics of research collaboration networks [ 63 ]. Uncertainty avoidance explains how cultures adjust to change and cope with uncertainty [ 62 ], and the pandemic has caused major changes and uncertainties at all levels of society worldwide [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bibliometric techniques have been used to present an overview of COVID-19 research. Efforts have been made to analyze the coverage of different data sources of COVID-19 publications [15][16][17], using altmetrics (ie, Wikipedia and Mendeley) [18,19], analyzing the effectiveness and impact of collaboration [20,21],…”
Section: State-of-the-art and Previous Bibliometric Studiesmentioning
confidence: 99%
“…Bibliometric techniques have been used to present an overview of COVID-19 research. Efforts have been made to analyze the coverage of different data sources of COVID-19 publications [ 15 - 17 ], using altmetrics (ie, Wikipedia and Mendeley) [ 18 , 19 ], analyzing the effectiveness and impact of collaboration [ 20 , 21 ], gender differences [ 22 ], topic evolution [ 16 , 23 ], scholarly communication flow during this pandemic [ 24 , 25 ], as well as OA of these research outputs[ 5 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has also caused delays in the completion of research initiatives [1]. Complex changes in research publication patterns and collaboration networking have been reported [2]. Several recent studies have examined the influence of the COVID-19 pandemic on research output such as on biomedical publishing patterns noting a significant reduction in international collaboration [3].…”
Section: Introductionmentioning
confidence: 99%